HUBUNGAN ANTARA KEPERCAYAAN DIRI DENGAN PENYESUAIAN DIRI MAHASISWA ETNIS PAPUA ANGKATAN 2018 DI UNIVERSITAS KRISTEN SATYA WACANA SALATIGA (PSIKOLOGI KONSELING, 2020)
This research aims to find out the relationship between self-confidence and self-adjustment of Papuan ethnic students™ class of 2018, which originally from Timika regency in Satya Wacana Christian University. The subjects in this study were 40 active students. The Sampling technique used is Purposive Sample with criteria, minimum age 17-21, active students™ status, come from the Timika regency area, first time wander off. The data collection method used the Likert scale method, pervade the scale of self-adjustment referred to The Student Adaptation to College Questionnaire (SACQ) discovered by Baker (2002), and the self-confidence scale that refers to the theory that stated by Lauster (2012). Manage data using analysis Product Moment Correlation and assisted using software SPSS 22.0 for Windows. The results of the study showed a significant positive relationship between self- confidence and self- adjustment was 0.589 with significant value 0,000. This shows that, the higher self- confidence is owned by 2018 Papuan ethnic students from the Timika regency, the better the self-adjustment they make, conversely the lower the self- confidence they have, the more difficult the self-adjustment they make.Key words: Self-Adjustment; Self Confidence.